Current State and Development of the Accommodation Business in LuangPrabang - OUTTHACHACK, Sindavone; SOMSAMONE, Vilayphone; THIDAVANH, soulichanh; VONGMANICHANH, nouy (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The study of the Current State and Development of the Accommodation in Luang Prabang, there are 2 objectives of research: 1) the Current Situation of the Accommodation business in Luang Prabang, 2) the government policy towards the development of the Accommodation Business in Luang Prabang. Results of a study of facilities during the period 2005-2017 found that the number of accommodations grew by 276, but the total number of bedrooms increased by 3,334 rooms, with the total number of beds increasing to 5,708 units. Of these, the total number of double beds increased to 1,637 units, with the total number of beds increased to 1,447, with the total number of single beds being 214. According to statistics and data, the development or expansion of accommodation is still small, but the development of the hotel will be further expanded by increasing the number of bedrooms, beds and the environment to attract more clients. Human Resource Development in Tourism Sector, the authorities of Luang Prabang province have been given serious consideration. From Figure 1 shows that there were 62,951 Lao and indirect tourism workers in 2016, with nearly 20% direct labor, while in 2017 there were 701 direct and indirect labor, with 2% more direct labor compared to the previous year. From Figure 2, it shows that in 2017, from the direct labor force to the tourism sector, the total occupancy rate was 25%. Tourism revenue in Luang Prabang, Luang Prabang, in 2005 was US 14,024,745. As of 2011, there were 96,077,100, which saw an increase of US 82,052,355. As of 2017, there were 174,515,598 revenues. Compared to 2011, the amount of US 78,438,498 saw that tourism revenue was steadily increasing and was able to generate a full source of revenue.